Screening for Substance Abuse: Good Idea or Not Ready for Prime Time? - Andrea Truncali; Jennifer McNeely; Laura Huben; David Kerr; Madeline Naegle; Marc Gourevitch (Association of American Medical Colleges, 2011)
Abstract This resource is a web-based module that introduces the practice of screening for substance abuse in health care settings and considers the question of when to implement a screening program. It reviews existing standards of screening for substance abuse and asks whether health systems should expand current practices to ask about use of drugs besides alcohol and tobacco. In addition, the module provides in-depth teaching on the key concepts of sensitivity, specificity, and predictive values. The module is multimedia and delivers the above content through the use of video, text, graphics, and voiceover, as well as questions followed by expert and peer feedback. Medical, dental, and nursing students in our research mentorship program were asked to complete the module as part of their summer experience. Evaluation of this pilot revealed that almost all of the students thought the module was easy to navigate; dealt with a subject of interest; covered most of the expected topics; was clear, logical, and orderly; and had the right balance of multimedia. Students felt challenged by the material and stated that it raised questions they had not previously considered about the practice of screening and the interpretation of screening test results. This module is one of six in a series created for the New York University Substance Abuse Research Education and Training Program. The program is a National Institute on Drug Abuse-funded initiative whose aim is to enhance interest in substance abuse research among health professional students, including, but not limited to, students in medicine, nursing, and dentistry.